Synthesis and Performances of Si-Carboxymethyl Starch Sodium as a Filtrate Reducer - Zhuang, Jia; Liu, Dong; Wang, Jian-Ming; Li, Lin-Feng (Asian Journal of Chemistry, 2013)
A new modified starch (Si-carboxymethyl starch sodium, Si-CMSS) as filtrate reducer for drilling fluid was synthesized by the reaction of silicate and carboxymethyl starch sodium(CMSS). The phase and structure of synthetic product were characterized by X-ray diffraction and Fourier transform infrared spectrum, silicon-hydrogen groups were found in the molecular structure of the product, indicating that silicate was involved in the reaction. As a filtrate reducer, Si-carboxymethyl starch sodium had good filtration control and environmental performance, more importantly, its temperature resistance performance was obviously increased to 150 ºC. The filtering mechanism of Si-carboxymethyl starch sodium was analyzed and discussed for the first time.